Tourism Objects as Social Studies Learning Sources in Elementary School - Putri Rachmadyanti; Elsinora Mahananingtyas; Lita Ariyanti (Journal Of Teaching And Learning In Elementary Education, 2022)
Objects tourism in premises increasingly growing and provide impacts positively on the economy of the community. The existence of tourist attractions can also contribute to the world of education, especially as a source of learning. Purpose research is the exploration use of tourism attractions in learning in Elementary School Education. The method of research that is used is research qualitative study of the case. The data collection technique used two steps, namely questionnaires and semi-structured interviews. The participants were 89 elementary school teachers in 6 cities of East Java who filled out a questionnaire and 12 people were willing to do semi-structured interviews. The findings in this study are 59% of teachers use the type of natural tourism object in learning, 55% of teachers choose tourism objects based on teaching materials, 55% of teachers use tours to make learning more fun, and 52% of teachers explain the obstacles to learning by utilizing these attractions come from costs. The study is expected to give a contribution positive to the development of learning that is based on experience in the School Elementary with tourism objects. This study also emphasizes the importance of providing effective learning resources for social studies learning in elementary schools.